2003
DOI: 10.1034/j.1600-0706.2003.12407.x
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of a range expansion: changes in cranial morphology and rates of energy extraction for North American red squirrels from different latitudes

Abstract: 2003. The anatomy of a range expansion: changes in cranial morphology and rates of energy extraction for North American red squirrels from different latitudes. -Oikos 102: 33 -44.Species with expanding ranges provide unique opportunities to examine environmentally induced adaptations in ecological traits and anatomical characteristics. Since the late 1800s, the North American red squirrel (Tamiasciurus hudsonicus) has expanded its range into the central hardwoods of the United States in conjunction with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Likewise, Boutin and Larsen (1993) report heavier squirrels in spruce habitat relative to pine habitat (Pinus banksiana), a difference of approximately 35-40 g for both males and females, but larger squirrels from spruce habitat were sampled further north (Yukon) than squirrels from pine habitat (Alberta), suggesting a latitudinal effect. In contrast, Smith (1970) found heavier squirrels in pine habitat (T. hudsonicus X ¼ 243.9 g) versus those caught within other conifer habitats (T. hudsonicus X ¼ 229.0 g; T. douglasii X ¼ 209.9 g), and Lindsay (1986) found a similar multivariate result for T. douglasii; larger squirrels associated with larger, tougher cones (also see Goheen et al [2003] for similar results in nutproducing forests). Published literature presents mixed results regarding squirrel size and cone serotiny.…”
Section: Discussionsupporting
confidence: 48%
“…Likewise, Boutin and Larsen (1993) report heavier squirrels in spruce habitat relative to pine habitat (Pinus banksiana), a difference of approximately 35-40 g for both males and females, but larger squirrels from spruce habitat were sampled further north (Yukon) than squirrels from pine habitat (Alberta), suggesting a latitudinal effect. In contrast, Smith (1970) found heavier squirrels in pine habitat (T. hudsonicus X ¼ 243.9 g) versus those caught within other conifer habitats (T. hudsonicus X ¼ 229.0 g; T. douglasii X ¼ 209.9 g), and Lindsay (1986) found a similar multivariate result for T. douglasii; larger squirrels associated with larger, tougher cones (also see Goheen et al [2003] for similar results in nutproducing forests). Published literature presents mixed results regarding squirrel size and cone serotiny.…”
Section: Discussionsupporting
confidence: 48%
“…2008). This very proximate measure of performance speaks to the direct interaction between an organism and its environment, and field studies have demonstrated the rapid evolution of bite force in populations that encounter selection for a more resistant diet (Goheen et al. 2003; Herrel et al.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of feeding, bite force is often used as a performance variable because it reflects the potential breadth of an animal's diet based on food hardness (Anderson et al 2008). This very proximate measure of performance speaks to the direct interaction between an organism and its environment, and field studies have demonstrated the rapid evolution of bite force in populations that encounter selection for a more resistant diet (Goheen et al 2003;Herrel et al 2008). The question is, how do FEA-based measures of mechanical performance relate to aspects of organismal performance that are seen by natural selection?…”
Section: Discussionmentioning
confidence: 99%
“…Squirrels (Sciurus spp.) are recognized as important predators of pollen and seed cones (Hurly et al 1987) and have the capacity to reduce seed availability and to influence forest regeneration (Gill et al 1995;Goheen et al 2002). In TNNP, Boa-Antwi (2009) documented a 66% reduction in balsam fir seed from the combined effects of cone predation by red squirrels and cone/seed eating insects during a season of high cone production.…”
Section: Pre-dispersal Seed Predationmentioning
confidence: 97%